Adsorção de antibióticos em meio aquoso utilizando diferentes adsorventes - Silva, Niléia Cristina da [UNESP] (2015)
The presence of pharmacological compounds in water supply sources are a risk as to the quality of water intended for human consumption. The introduction of these compounds into the environment through anthropogenic sources is a latent risk to aquatic and terrestrial organisms. Some studies report to reduced effectiveness in removing the drugs present in raw water during its treatment in a Water Treatment Plant. Given this aspect, the present study evaluated the removal capacity of antibiotics ampicillin, amoxicillin, cephalexin and ciprofloxacin, via adsorption process in batch and column using the following adsorbents: plastic bottles (after use), sugar cane bagasse (SCB), functionalized clay with N-dodecyl-2- pyrrolidone (Mo-DDP), silica and oligomer polyhedral of organo silsesquioxane modified with thiourea (SG- TU and POSS-TU, respectively), and silica modified by cyclodextrin (β- CDSi). The adsorbents were characterized by Boehm titration, FTIR, pH zero point of charge (pH ZPC ) and SEM. The drug concentrations were determined by high performance liquid chromatography. The adsorption parameters tested showed that 120‟ to 240‟ of contact are sufficient for adsorbent adsorption in the adsorbents which the solution initial pH interferes in the adsorption in different magnitudes, depending on the adsorbent-adsorbate system rated. The adsorption balance batched was expressed through isotherms adsorption according to Langmuir, Freundlich, Temkin and D-R. The Freundlich isotherm was the one that best represented the experimental data for all adsorbents, except for β-CDSi, which had the best adsorption equilibrium represented by the Langmuir model. The kinetics of drugs adsorption was discussed using the kinetic models of Pseudo-first and second order, Elovich, intraparticle diffusion and film diffusion. The Pseudo-second kinetic model can better describe the adsorption of antibiotics in the ...